Association of Body Mass Index, Age, and Sex with Blood Glucose Levels in Type 2 Diabetes Mellitus Patients - Arsana, Bagus Surya; Bagiansah, Mamang; Zoraya, Sabrina Intan; Azhar, Mutiara Budi (Jurnal Biologi Tropis, 2024)
People with diabetes mellitus (DM) experience impaired insulin function so that glucose cannot enter the cells so that blood glucose levels increase. Several factors such as body mass index, age, and gender can also affect blood glucose levels. If not controlled properly, high blood glucose levels can cause various complications. The purpose of this study was to analyze the relationship between body mass index, age, and gender with blood glucose levels in patients with type 2 diabetes mellitus at the Internal Medicine Polyclinic, Praya Regional General Hospital (RSUD). The design of this study is cross-sectional and observational. With a sample size of 108, sequential sampling was the method used. The Continuity Correction test and the Chi-Square test were used to analyze the data. The study's findings revealed a highly significant correlation between blood glucose levels and body mass index (p-value <0.001, OR 11.261, 95% CI 4.137-30.649). Blood glucose levels and age are significantly correlated (p-value = 0.018, OR 2.865, 95% CI 1.269-6.466). Blood glucose levels and gender are significantly correlated (p-value = 0.004, OR 3.567, 95% CI 1.575-8.077). In patients with type 2 diabetes mellitus at the Internal Medicine Polyclinic of Praya Hospital, random blood glucose levels were significantly correlated with body mass index, age, and gender, according to the findings of statistical tests. Uncontrolled random blood glucose levels were eleven times more common in obese respondents than in non-obese respondents.